Application of FTIR and Raman spectroscopy to characterisation of bioactive materials and living cells. Issue 2 (2003) - Notingher Notingher, I. I.; Jones Jones, J. R. J. R.; Verrier Verrier, S. S.; Bisson Bisson, I. I.; Embanga Embanga, P. P.; Edwards Edwards, P. P.; Polak Polak, J. M. J. M.; Hench Hench, L. L. L. L.
Abstract : Both Fourier Transform Infrared (FTIR) and Raman spectroscopy have been applied to the in vitro characterisation of biomaterials, mainly surface reactions leading to the formation of a biologically active hydroxycarbonate apatite (HCA) layer on the sample surface when immersed in simulated body fluids (SBF). The HCA layer indicates the degree of bioactivity of the sample, because it leads to a strong bond between the biomaterial and living tissue. Reflection measurements using FTIR allow quick, non-destructive detection of the HCA layer for solid and powder samples. Due to the low Raman scattering efficiency and low absorption of water in the visible-near infrared region, Raman micro-spectroscopy was successfully used for the in situ characterisation of 20 and 40 µ m diameter 45S5 Bioglass ® fibres. The in situ capabilities of the Raman micro-spectrometer have also been extended to the characterisation of living cells attached on bioinert silica and bioactive 45S5 Bioglass ® and 58S substrates. Using a high power 785 nm laser, living cells in physiological conditions can be real-time sampled over long periods of time without inducing cell damage and with good signal strength. Cell death can be monitored because it proved to induce strong changes in the Raman signature in the spectral regions 1000–1150 cm –1 and 1550–1650 cm –1 .